1970
DOI: 10.1073/pnas.66.4.1206
|View full text |Cite
|
Sign up to set email alerts
|

Axon Growth: Roles of Microfilaments and Microtubules

Abstract: Abstract. The motile tips of elongating axons consist of growth cones from which microspikes protrude. Cytochalasin B causes retraction of microspikes, rounding-up of growth cones, and cessation of axon elongation. Drug withdrawal is followed by resumption of growth cone and microspike activity and of axon elongation. In contrast, colchicine causes shortening and retraction of axons, but it does not initially affect the tips. Growth cones and microspikes of elongating axons contain a network of 50 A microfilam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
210
0

Year Published

1972
1972
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 435 publications
(222 citation statements)
references
References 15 publications
12
210
0
Order By: Relevance
“…Microtubules play a key role in axonal growth and guidance (Yamada et al, 1970;Forscher and Smith, 1988;Suter et al, 1998;Dent et al, 1999;Dent and Gertler, 2003). They form the backbone of the axonal shafts and core domain of growth cones, giving stability to those structures and enabling organelle transport (Hirokawa and Takemura, 2005).…”
Section: Retraction Bulbs Contain Disorganized Microtubulesmentioning
confidence: 99%
“…Microtubules play a key role in axonal growth and guidance (Yamada et al, 1970;Forscher and Smith, 1988;Suter et al, 1998;Dent et al, 1999;Dent and Gertler, 2003). They form the backbone of the axonal shafts and core domain of growth cones, giving stability to those structures and enabling organelle transport (Hirokawa and Takemura, 2005).…”
Section: Retraction Bulbs Contain Disorganized Microtubulesmentioning
confidence: 99%
“…Cytochalasin B (CB)I (1) causes the disruption of microfilaments in the cleavage furrow of marine eggs end HeLa cells (2)(3)(4), and the reversible disorganization of microfilaments in several types of embryonic cultures (5)(6)(7)(8) . It has been suggested that these microfilaments are involved in primitive contractile processes and that they are similar to actin (8)(9)(10) .…”
Section: Introductionmentioning
confidence: 99%
“…These movements seem to be related to a membraneassociated microfilament system (14,27,28,36,38) that has frequently been shown to contain actin (2,22,24,29,30). Many morphological studies showing disruption of thin filament arrays (3,6,7,18,31,32,39,40) and a few studies with purified actin (16,21,33,34) or myosin (footnote 2 and reference 26) suggest that cytochalasins can interact directly with proteins of the microfilament system. However, because of the multiple and sometimes contradictory effects of cytochalasins (4,5,8,12), no in vivo effect has yet been related unambiguously to direct interaction with the microfilament system.…”
mentioning
confidence: 99%